2014
DOI: 10.1371/journal.pntd.0002927
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Leptospirosis Transmission in an Urban Slum Community: Role of Poor Environment in Repeated Exposures to the Leptospira Agent

Abstract: BackgroundLeptospirosis has emerged as an urban health problem as slum settlements have rapidly spread worldwide and created conditions for rat-borne transmission. Prospective studies have not been performed to determine the disease burden, identify risk factors for infection and provide information needed to guide interventions in these marginalized communities.Methodology/Principal FindingsWe enrolled and followed a cohort of 2,003 residents from a slum community in the city of Salvador, Brazil. Baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
172
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(203 citation statements)
references
References 40 publications
(90 reference statements)
15
172
1
8
Order By: Relevance
“…This study found that leptospirosis prevention practice scores increased significantly with increasing age and household income among non-agricultural workers. The risk of leptospirosis infection is commonly reported among younger and low-income groups [57][58][59]. Considering that younger and lower-income groups were less likely to engage in leptospirosis prevention practices, a more concerted effort of changing the health behavior of these groups would be beneficial in reducing the risk and potential economic burden of leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that leptospirosis prevention practice scores increased significantly with increasing age and household income among non-agricultural workers. The risk of leptospirosis infection is commonly reported among younger and low-income groups [57][58][59]. Considering that younger and lower-income groups were less likely to engage in leptospirosis prevention practices, a more concerted effort of changing the health behavior of these groups would be beneficial in reducing the risk and potential economic burden of leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…21,26 In 2003, Salvador's Oswaldo Cruz Foundation (FIOCRUZ) established a study site within this community for a cohort study of urban leptospirosis. [29][30][31] A household census by FIOCRUZ at that time identified 14,867 residents in 3068 households within the 0.46 km 2 study area.…”
Section: Study Populationmentioning
confidence: 99%
“…Concuerdan además nuestros resultados con los obtenidos por Céspedes et al (2003) quienes al identificar factores de riesgos en la población humana de la provincia Manu, Perú, plantearon que la infección por Lepstospira presentó una tendencia homogénea entre los distintos grupos etarios, aunque el número de seropositivos fue mayor en las personas de edad laboral. Según Felzemburgh et al (2014) aunque el género masculino no fue identificado como un factor de riesgo de infección por Leptospira en un estudio de cohorte realizado en un área rural, los varones tienen un riesgo significativamente superior para adquirir leptopirosis. De acuerdo con Alavi & Khoshkho (2014) en las recientes décadas la leptospirosis ha sido considerada como una enfermedad infecciosa emergente que constituye un problema importante de salud pública a nivel mundial, que se presenta en ambientes urbanos, así como también en regiones rurales.…”
Section: Materials Y Métodos Resultados Y Discusiónunclassified